Ciblon: Media for Socialization of Children in Pengging Village - Ismail S, Pramudito; Setyono, Budi (GETER : Jurnal Seni Drama, Tari dan Musik, 2024)
This research explores the unique cultural activity of ciblon, where children in Pengging Village produce rhythmic sounds by skillfully playing with water. This practice, deeply ingrained in their daily lives, serves as both a playful activity and a medium for cultural expression. The study aims to examine the process of children engaging in ciblon, identify the musical elements and techniques involved, and analyze how this activity facilitates socialization among participants. Using a qualitative approach with a social framework based on socialization theory, data were collected through observation, interviews, and documentation, followed by systematic analysis. The findings reveal that ciblon not only embodies intricate rhythmic structures created through water and hand movements but also serves as a dynamic space for fostering communication, collaboration, and the transmission of cultural values. By intertwining play, music, and social interaction, ciblon contributes to the development of social skills and strengthens community bonds, highlighting its significance as both a cultural heritage and an educational tool for shaping the social and cultural fabric of Pengging Village.